Route Planning for Flexible Bus Services in Regional Cities and Rural Areas: Combining User Preferences with Spatial Analysis - Stefanos Tsigdinos; Christos Karolemeas; Maria Siti; Kalliopi Papadaki; Konstantinos Athanasopoulos; Panagiotis G. Tzouras (Future Transportation)
Flexible public transport is defined as a future mobility solution that adapts to user needs and the fluctuating demand patterns that mainly appear in rural areas. However, the temporal variations in traveler preferences for flexible bus services remain largely unexplored in existing research. This constrains the realization of adaptive and customized solutions. Therefore, this study attempts to develop a distinct method for strategic planning of a flexible bus service. To this end, a combinatorial method is undertaken: quantitative social research (questionnaires) and spatial analysis. This combinatorial approach is applied at Korinth and Loutraki in Greece, two significant rural areas neighboring the Athens Metropolitan Area. The results signify that cost and time are the most crucial factors affecting the use of a flexible service. Furthermore, respondents preferred a door-to-door service in the morning and a stop-based service in the afternoon/evening. Concerning route planning, eight routes with different purposes are suggested (e.g., train feeder, touristic, etc.) covering adequately both urban and rural parts of the study area. Notably, the applied methodological approach can be a guideline for planners and policymakers, assisting them in finding effective strategies for introducing flexible public transport in rural areas, especially in contexts where collective transport culture is limited.